Fundamental view of the outcomes of entrepreneurship education - I. Kozlinska (Estonia, 2022)
The research paper presents a holistic framework of the outcomes of entrepreneurship education (EE) at educational and socio-economic levels. Employing the general scientific research methods, monograph and logical construction, the author investigates the fundamental origins of the European Competence Framework for entrepreneurial learning and identifies a scientific justification for its implementation. This work is also the first to exploit an integral view of entrepreneurship as a combination of employability, intrapreneurship and venture creation – for measuring the impact of entrepreneurship education, and to set linkages between learning outcomes in real life and educational settings. The target audiences for this paper include entrepreneurship educators, researchers and EE decision-makers.